The Role of Islamic Finance in Sustainable and Green Transition - Ahmed, Ubaid; Maruf, Aminudin; Alam, Shahbaz; Azizah, Lutfiatul (Universitas Muhammadiyah Surakarta, 2024)
This study examines the role of Islamic finance in advancing the United Nations' Sustainable Development Goals (SDGs), focusing on often-overlooked conflicts among these goals, such as the tension between poverty alleviation (SDG 1), hunger eradication (SDG 2), and environmental sustainability. It emphasizes the need for balanced progress across SDGs, particularly in Muslim societies where welfare aligns with religious principles. The study advocates for a Green Economic Transition (GET) aimed at achieving high human development while respecting Maqasid Shariah and ecological limits. GET, it suggests, should be the core of climate-conscious policies and business strategies. Recognizing shifts in the global financial system to reconcile economic and social development with environmental goals, the study underscores the need for policies aligning these aspects. It also explores the contribution of Islamic economics and finance-including commercial finance (banking, takaful, Sukuk, Shariah-compliant equity markets) and social finance (Zakah, Waqf, charities, Qard)-in fostering sustainable green finance. Noting the gap where these tools are still tied to conventional finance, the study proposes a framework for developing coherent climate policies within Islamic finance and identifies opportunities for Islamic sustainable green finance.